2016
DOI: 10.1128/aem.03410-15
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Variability of the Exosporium Layer of Clostridium difficile Spores

Abstract: The anaerobic sporeformer Clostridium difficile is the leading cause of nosocomial antibiotic-associated diarrhea in developed and developing countries. The metabolically dormant spore form is considered the transmission, infectious, and persistent morphotype, and the outermost exosporium layer is likely to play a major role in spore-host interactions during the first contact of C. difficile spores with the host and for spore persistence during recurrent episodes of infection. Although some studies on the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 26 publications
5
82
0
Order By: Relevance
“…The composition of the exosporium layer of C. difficile spores has been recently identified (19), revealing a complex composition of 184 proteins, among which several proteins known to be involved in pathogenesis and evasion of immunity in other pathogens were identified (e.g., elongation factor Tu and alpha-enolase) (19). Notably, our recent results have shown that during spore formation, C. difficile is capable of producing spores with two distinctive morphotypes of the exosporium layer, either thin or thick (13). However, whether these two different morphotypes of the exosporium layer emerge directly from the mother cell and whether these two morphotypes are formed during biofilm development remain unclear.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…The composition of the exosporium layer of C. difficile spores has been recently identified (19), revealing a complex composition of 184 proteins, among which several proteins known to be involved in pathogenesis and evasion of immunity in other pathogens were identified (e.g., elongation factor Tu and alpha-enolase) (19). Notably, our recent results have shown that during spore formation, C. difficile is capable of producing spores with two distinctive morphotypes of the exosporium layer, either thin or thick (13). However, whether these two different morphotypes of the exosporium layer emerge directly from the mother cell and whether these two morphotypes are formed during biofilm development remain unclear.…”
mentioning
confidence: 86%
“…In this context, recent studies have revealed that the ultrastructure of C. difficile spores is similar to that of other Gram-positive bacteria (13,14). The outermost layer is an electron-dense layer that, in most epidemic strains, is covered by hair-like projections and has been shown to be ultrastructurally stable (13).…”
mentioning
confidence: 97%
See 3 more Smart Citations